2021
DOI: 10.3389/fpls.2021.741342
|View full text |Cite
|
Sign up to set email alerts
|

A Valsa mali Effector Protein 1 Targets Apple (Malus domestica) Pathogenesis-Related 10 Protein to Promote Virulence

Abstract: To successfully colonize the plants, the pathogenic microbes secrete a mass of effector proteins which manipulate host immunity. Apple valsa canker is a destructive disease caused by the weakly parasitic fungus Valsa mali. A previous study indicated that the V. mali effector protein 1 (VmEP1) is an essential virulence factor. However, the pathogenic mechanism of VmEP1 in V. mali remains poorly understood. In this study, we found that the apple (Malus domestica) pathogenesis-related 10 proteins (MdPR10) are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…However, the interaction between VmEP1 and MdPR10, a target protein of VmEP1 (Wang et al, 2021), did not result in degradation of MdPR10 (Figure S2), indicating that VmEP1 specifically promotes MdKRBP4 degradation. These results indicate that the interaction between VmEP1 and MdKRBP4 reduces MdKRBP4 accumulation by promoting its degradation.Previous studies have shown that VmEP1 interacts with MdPR10, an immune-related protein(Wang et al, 2021). In the present study,…”
supporting
confidence: 53%
See 4 more Smart Citations
“…However, the interaction between VmEP1 and MdPR10, a target protein of VmEP1 (Wang et al, 2021), did not result in degradation of MdPR10 (Figure S2), indicating that VmEP1 specifically promotes MdKRBP4 degradation. These results indicate that the interaction between VmEP1 and MdKRBP4 reduces MdKRBP4 accumulation by promoting its degradation.Previous studies have shown that VmEP1 interacts with MdPR10, an immune-related protein(Wang et al, 2021). In the present study,…”
supporting
confidence: 53%
“…Meanwhile, the expression levels of ROS accumulation-regulating genes (Figure 2c) and salicylic acid pathway-related genes, such as MdPR1, MdPR2, and MdPR5 (Figure 2d), were considerably enhanced 3 days post-infiltration. The relative transcript level of MdPR10, a target of VmEP1 (Wang et al, 2021), was also enhanced in apple leaves expressing MdKRBP4 (Figure 2d). These results suggest that the transient expression of MdKRBP4 activates the plant immune response and induces ROS accumulation.…”
Section: Overexpression Of Mdkrbp4 Activates the Immune Responsementioning
confidence: 91%
See 3 more Smart Citations